Strategic and Financial Evaluation of Spin-Off Structures in a State-Owned Aerospace Enterprise: A Case-Based Simulation Study - Kevin Rizky Hidayat; Taufik Faturohman (Journal Integration of Social Studies and Business Development, 2025)
This study assesses the financial feasibility and strategic implications of corporate spin-offs within state-owned enterprises (SOEs) in emerging markets, focusing on a capital-intensive aerostructure division within a national aerospace firm. Despite the extensive literature on corporate restructuring in developed economies, ex-ante quantitative analysis of SOE spin-offs remains limited, particularly in the aerospace sector. This research addresses that gap by evaluating two ownership structures—a wholly-owned subsidiary (Scenario 1) and a 60/40 joint venture (Scenario 2)—through a five-year Discounted Cash Flow (DCF) valuation complemented by Monte Carlo simulation. The results indicate that while both models are financially viable, the joint venture structure yields a superior intrinsic equity value of 1.30 times the initial capital, offering a 14.4% premium over the subsidiary model. This advantage is attributed to operational synergies that raise the division’s Return on Invested Capital (ROIC) to an average of 16.05%, surpassing the Weighted Average Cost of Capital (WACC) benchmark. Monte Carlo simulations confirm the robustness of this scenario, with a mean expected equity value 29% higher than the base case. Theoretically, the study contributes to corporate finance and restructuring literature by integrating Agency Theory, the Resource-Based View, and Trade-Off Theory to explain how joint ventures can mitigate agency costs, enhance resource access, and optimize capital structure in SOEs. These findings offer empirical insights into the design of spin-off strategies under ownership constraints typical of emerging market institutions.